Proceso de atención nutricional en paciente femenino de 20 años de edad con nefritis lúpica. - Quiñonez Mera, Emanuel Josué (2023)
This case study is based on a 20-year-old female patient who was diagnosed with Lupus Nephritis. Lupus erythematosus is an autoimmune disease of unknown origin, where the body does not recognize infectious agents and can attack itself, it is also multisystemic, and its outbreaks can be mild or severe. The objective of this study is to improve the nutritional status of the patient through nutritional intervention. Using indicators of anthropometric data, biochemical data, physical examination through clinical and dietary data through the analysis of food consumption. Once the nutritional assessment of the patient was carried out, it was possible to verify that she presents a Body Mass Index below normal, in addition, her biochemical tests reflect a high renal function, indicating her renal failure in the same way, the electrolytes are found with high values. It was also possible to show that leukocytes and lymphocytes are elevated, which may indicate that there is some type of infection, total cholesterol is also elevated, and hemoglobin and hematocrit levels are very low. The patient presents physical signs of nutritional deficiencies related to food and associated with lupus nephritis disease. Therefore, a renal diet is prescribed, since he is undergoing peritoneal dialysis, and a nutritional supplement is recommended to compensate for his requirements since he has no appetite.